Kepemimpinan Instruksional Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di SMP Negeri 1 STTU Julu Pak Pak Bharat - Banurea, Tumpak; Elfrianto, Elfrianto; Amiruddin, Amiruddin (Jurnal Manajemen Pendidikan Dasar, Menengah dan Tinggi [JMP-DMT], 2024)
The aim of this research is to find out: the Principal's Instructional Leadership in Improving the Quality of Education at State Middle School 1 STTU Julu Pakpak Bharat. 2. Obstacles to the Principal's Instructional Leadership in Improving the Quality of Education at State Middle School 1 STTU Julu Pakpak Bharat. 3. Solutions to overcome obstacles to the principal's instructional leadership in improving the quality of education at STTU Julu Pakpak Bharat State Middle School. The research was conducted from November 2023 to December 2023. This research method was qualitative. Data collection techniques were carried out using interviews, documentation and observation. The subjects of this research were teachers, students and school principals. The data analysis techniques in this research are data presentation, data reduction, and presentation of conclusions. The results and conclusions of this research are: 1) The principal's instructional leadership in improving the quality of education at State Middle School 1 STTU Julu Pakpak Bharat has been well implemented where teachers must carry out work discipline, then the principal demands teachers to prepare administration in learning, targeting students to achieve grades according to the KKM and teachers are required to be able to use learning media in learning and adapt to changes in the curriculum. 2) The obstacle to the Principal's Instructional Leadership in Improving the Quality of Education at SMP Negeri 1 STTU Julu Pakpak Bharat is the teacher's lack of ability to utilize learning facilities due to teacher unpreparedness. The principal as an instructional leader does not always carry out supervision duties for his teachers. If they conduct classroom observations, they do not provide post-observation feedback. Some of the reasons are the high managerial, administrative and teaching workload of school principals. As a result, school principals carry out supervision only to comply with system administration or government regulations. 3) The solution to overcome the obstacles to the Principal's instructional leadership in improving the quality of education at SMP Negeri 1 STTU Julu Pakpak Bharat is that the principal must improve collaboration with teachers, teachers increase their work motivation, the principal regularly carries out class visits and conducts evaluation meetings every month.